The Influence of Product Quality, Price, and Service Quality on Customer Satisfaction and Repurchase Intention at Jagar Coffee and Eatery Medan - Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring; David Pranata Pakpahan (Journal of Business Management, 2026)
This study aims to determine and analyze the influence of product quality, price, and service quality on customer satisfaction and repurchase intention at Jagar Coffee and Eatery. This research is an associative study utilizing quantitative data. The population in this study consists of all customers of Jagar Coffee and Eatery, the exact number of whom is unknown. The sample size for this research is 151 respondents. The sampling technique employed is purposive sampling, with the criteria that respondents must have previously made a purchase at Jagar Coffee and Eatery and are at least 17 years old. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study indicate that product quality and service quality have a direct, positive, and significant effect on customer satisfaction, whereas price does not have a significant effect on customer satisfaction. Product quality, price, and service quality do not have a direct, significant effect on customer repurchase intention. Customer satisfaction has a positive and significant effect on customer repurchase intention. Indirectly, product quality and service quality have a positive and significant effect on repurchase intention through customer satisfaction. Meanwhile, price does not have a significant effect on repurchase intention through customer satisfaction.